2000
DOI: 10.1002/1096-9071(200008)61:4<433::aid-jmv4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic study of HBsAg and HBeAg in saliva samples from patients with hepatitis B infection: Diagnostic and epidemiological significance

Abstract: Analysis of 505 cases history of patients among men with viral hepatitis demonstrates that HBV infected patients represent 68.9% of the total and that a non-parenteral rate of transmission is the most likely means of hepatitis B infection. Saliva and serum testing for the presence of specific HBV markers (HBsAg, HBeAg and HBV DNA) at different phases of the infection process were carried out to review the diagnostic and epidemiological value of saliva samples from patients with acute viral hepatitis B. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…The ELISPOT assay using the P815 mastocytome cell line pulsed with the CD8 + -restricted HBs (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) peptide indicated that nasal immunization with the combined HBs and HBc formulation activates antigen specific CD8 + cells, consistent with a strong Th1 response. This result is in line with the finding that B cells that bind viral capsids can prime cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ELISPOT assay using the P815 mastocytome cell line pulsed with the CD8 + -restricted HBs (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) peptide indicated that nasal immunization with the combined HBs and HBc formulation activates antigen specific CD8 + cells, consistent with a strong Th1 response. This result is in line with the finding that B cells that bind viral capsids can prime cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…38 Recent reports from Bertoletti et al reveal an important degree of T-cell functional recovery after antiviral treatment with Lamivudine. 39,40 This suggests that it is possible to rescue T cells from non-responsive states. Other reports demonstrate that in patients naturally recovering from HBV chronic infection, there is a rebound in cellular immunity that correlates with viral clearance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations